2009
DOI: 10.1038/nsmb.1606
|View full text |Cite
|
Sign up to set email alerts
|

PKC maturation is promoted by nucleotide pocket occupation independently of intrinsic kinase activity

Abstract: The protein kinase C (PKC) Ser/Thr kinases account for approximately 2% of the human kinome and regulate diverse cellular behaviors. PKC catalytic activity requires priming phosphorylations at three conserved sites within the kinase domain. Here we demonstrate that priming of PKC is dependent on the conformation of the nucleotide binding pocket but not on its intrinsic kinase activity. Inactive ATP binding site mutants are unprimed, but they become phosphorylated upon occupancy of the ATP binding pocket with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 38 publications
7
126
0
Order By: Relevance
“…These and similar observations (23,(28)(29)(30)(31) have brought up the question about the functional role of ATP binding in pseudokinases. Here we have addressed this question in the JAK2 pseudokinase domain, focusing on its pathogenic mutants.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These and similar observations (23,(28)(29)(30)(31) have brought up the question about the functional role of ATP binding in pseudokinases. Here we have addressed this question in the JAK2 pseudokinase domain, focusing on its pathogenic mutants.…”
Section: Discussionmentioning
confidence: 92%
“…Protein kinase C, for example, has been shown to be regulated by noncatalytic nucleotide binding (30). Also, in the pseudokinases STRADα (28,36) and integrin-linked kinase (ILK) (23,31), ATP binding is required to enable critical protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data indicate that the conformation of the ATP-binding pocket can have a significant impact on catalytic-independent functions of kinases. For example, recent studies with Akt (16) and PKCε (21) suggest that binding to an ATP-competitive inhibitor potentiates membrane recruitment and the induction/stabilization of priming phosphorylation events. In the case of PKCε, priming phosphorylation events for the M486A gatekeeper mutant are compromised upon PMA-induced translocation to the plasma membrane (21).…”
Section: Discussionmentioning
confidence: 99%
“…Besides reductions in activity (k cat ), mutation of the gatekeeper to a small amino acid can have significant effects on substrate binding (K m ). For example, the M486A gatekeeper mutation of PKCε causes a marked decrease in priming site phosphorylation relative to wild type PKCε, an observation that has been attributed to a reduced affinity for ATP (21).…”
Section: Chemical Genetics | Irreversible Inhibitor | Sgk494mentioning
confidence: 99%
“…11 critical lysine in the ATP-binding site of these proteins results in increased susceptibility to phosphatases when expressed in cells, rather than defects in the ability of these mutants to autophosphorylate [58]. More recent evidence has demonstrated that the mammalian Target of Rapamycin (mTOR) pathway regulates TM phosphorylation of some, but not all, PKCs [59][60][61].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%